2017
DOI: 10.1093/hmg/ddx049
|View full text |Cite
|
Sign up to set email alerts
|

Sex specific activation of the ERα axis of the mitochondrial UPR (UPRmt) in the G93A-SOD1 mouse model of familial ALS

Abstract: The mitochondrial unfolded protein response (UPRmt) is a transcriptional program aimed at restoring proteostasis in mitochondria. Upregulation of mitochondrial matrix proteases and heat shock proteins was initially described. Soon thereafter, a distinct UPRmt induced by misfolded proteins in the mitochondrial intermembrane space (IMS) and mediated by the estrogen receptor alpha (ERα), was found to upregulate the proteasome and the IMS protease OMI. However, the IMS-UPRmt was never studied in a neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 46 publications
4
51
0
Order By: Relevance
“…Interestingly, previous studies identified sex-specific differences in mitochondrial function in SOD1 G93A mice that have been suggested to underlie female resilience in this line. Notably, female SOD1 G93A mice have increased activation of the mitochondrial unfolded protein response (UPRmt; Riar et al, 2017), reduced mitochondrial calcium accumulation (Kim et al, 2012) and improved preservation of Complex I function (Cacabelos et al, 2016). However, whether these sex-specific differences in mitochondrial function are mutation-or genetic-background-dependent remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies identified sex-specific differences in mitochondrial function in SOD1 G93A mice that have been suggested to underlie female resilience in this line. Notably, female SOD1 G93A mice have increased activation of the mitochondrial unfolded protein response (UPRmt; Riar et al, 2017), reduced mitochondrial calcium accumulation (Kim et al, 2012) and improved preservation of Complex I function (Cacabelos et al, 2016). However, whether these sex-specific differences in mitochondrial function are mutation-or genetic-background-dependent remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…74 Finally, oestrogen antagonises the P2X7 receptor 75 (overactivation of this receptor is believed to be involved in ALS neurotoxicity 76 ), offering further protection (at least at earlier stages of the disease) in female SOD1 G93A mice. 74 Finally, oestrogen antagonises the P2X7 receptor 75 (overactivation of this receptor is believed to be involved in ALS neurotoxicity 76 ), offering further protection (at least at earlier stages of the disease) in female SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these processes are also oestrogen receptor-dependent. 74 Finally, oestrogen antagonises the P2X7 receptor 75 (overactivation of this receptor is believed to be involved in ALS neurotoxicity 76 ), offering further protection (at least at earlier stages of the disease) in female SOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 99%
“…In mice subjected to hypoxia-ischemia, mitophagy induction is higher in females than in males and the lower clearance of damaged mitochondria in males may contribute to their greater vulnerability to neuronal death after hypoxia-ischemia [77]. Interestingly, the ERα-dependent UPRmt pathway is higher in females than in males [77, 78]. …”
Section: Factors Affecting Mitochondrial Quality Controlmentioning
confidence: 99%